Acoustic emission parameters and waveforms characteristics of fracture failure process of asphalt mixtures. (10th August 2019) - Qiu, Xin; Xu, Jingxian; Xiao, Shanglin; Yang, Qing
Highlights: Acoustic emission could diagnose the fracture failure process of asphalt mixtures. The wavelet coefficient of AE sequence is relevant to the damage evolution process. The AE energy could stably reveal the fractal characteristic of AE process. The waveform fractal dimension could identify the critical fracture condition. Abstract: Dynamical diagnosis of damage evolution is essential to promote the pavement performance of asphalt materials and prolong their service life. As a non-destructive method, acoustic emission (AE) can be used to assess the degree of deformation or cracking of stressed materials by detecting the energy release from damage points. The objective of the study was to explore the continuous damage evolution behavior of asphalt mixtures by evaluating the variation characteristics of AE parameters and waveforms. Firstly, the three-point bending tests and AE tests were simultaneously conducted on asphalt mixture beams, and AE behaviors associated with the failure process were investigated. Secondly, considering the impact of material heterogeneity on AE transmission, wavelet transform was utilized to qualitatively determine the relationship between wavelet coefficient and damage degree of asphalt mixtures. Lastly, the fractal theory was applied to quantitatively explore the scale-invariance of AE process and the AE mutation of damage process. The results show that the accumulation of AE energy and AE count could reflect the dynamical failure process of asphalt mixtures under different loading rates. The effect of sampling frequency could be presented by time-scale characteristics of AE waveforms. The fracture characteristics of asphalt mixtures could be reflected by amplitude and energy distribution of cumulative AE energy and AE waveforms. The fractal result of AE energy is relatively stable in revealing the flexural failure characteristics of asphalt mixtures. The mutational rise of the waveform fractal dimension from the minimum value is related to the critical fracture condition of asphalt mixtures.